Metabolites With Cytotoxic Activities From the Mangrove Endophytic Fungus Fusarium sp. 2ST2 - Chen, Yan; Wang, Guisheng; Yuan, Yilin; Zou, Ge; Yang, Wencong; Tan, Qi; Kang, Wenyi; She, Zhigang (Frontiers in Chemistry, 2022)
Two new 3-decalinoyltetramic acid derivatives with peroxide bridge fusarisetins E (1) and F (2), one new chromone fusarimone A (5), two new benzofurans fusarifurans A (9) and B (10), three new isocoumarins fusarimarins A–C (11–13), as well as five known analogues 3, 4, 6–8 and 14 were isolated from mangrove endophytic fungus Fusarium sp. 2ST2. Their structures and absolute configurations were established by spectroscopic analysis, density functional theory-gauge invariant atomic orbital NMR calculation with DP4+ statistical analysis, and electronic circular dichroism calculation. Compounds 1 and 2 showed significant cytotoxicity against human A549 cell lines with IC50 values of 8.7 and 4.3 μM, respectively.